The use of amaranth in the formulation of fishmeal culinary products for functional purposes - Ditrikh, Iryna; Kopovska, Angelica (My University, 2021)
Обґрунтована можливість використання борошна амаранту у рецептурі рибоборошняних кулінарних виробів для поліпшення органолептичних властивостей і підвищення біологічної цінності виробів.The possibility of using amaranth flour in the formulation of fishmeal culinary products has been substantiated to improve the organoleptic properties and increase the biological value of products.
Keywords: функціональні продукти; амарант; рибоборошняні кулінарні вироби; functional products; amaranth; fishmeal culinary products; кафедра готельно-ресторанної справи